(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The development of oratory skills in primary school teachers through speech culture formation is essential for effective pedagogy. This thesis examines linguistic, psychological, and pedagogical approaches to enhancing teachers’ communication. It explores structured training, interactive exercises, and ethical speech practices that improve engagement and clarity in teaching. By integrating speech culture into teacher education, educators can foster students’ cognitive and linguistic growth.